DEPRESSION, ANXIETY AND STRESS ASSOCIATED WITH WORK MOTIVATION OF INDONESIAN BANK EMPLOYEES IN THE NEW NORMAL DURING THE COVID-19 ERA - Eko Sujadi; Yuserizal Bustami; Muhammad Fadhli (Universitas Gunadarma, 2023)
Although there have been several studies investigated the effect of COVID-19 outbreak on mental health, studies that specifically analyze the impact of the COVID-19 outbreak on bank employees have not been investigated, especially during the new normal era. Therefore, this study aims to assess the mental health of bank employees and its correlation with dimensions of work motivation. This online cross-sectional study measured 403 participants using the DASS-21 and the MWMS scale. Participants who experienced depression, anxiety, and stress at the moderate to extremely severe level were 32.51%, 63.77%, and 7.94%. Furthermore, there are no differences in depression, anxiety, and stress on all demographic variables, except for the job position characteristics, which are significantly different on the anxiety scale. The correlation analysis results show that depression is negatively correlated with introjected regulation, identified regulation, and intrinsic motivation, whereas depression is positively correlated with the amotivation dimension; anxiety has a negative correlation with extrinsic regulation-material, introjected regulation, identified regulation, and intrinsic motivation; then stress is negatively correlated with the five dimensions including extrinsic regulation-social, extrinsic regulation-material, introjected regulation, identified regulation, and intrinsic motivation. These findings suggest that banks in Indonesia should provide mental health interventions for employees.